137k views
2 votes
Number One)

Solutions please:
f(x)= (x−1)^2−36
____________________________________________________________________
Number Two)
Harry solved a quadratic equation. His work is shown below.
In which step did Harry make an error?

Original: (x−5) ^2+6=42

Step One:(x−5)^2=36

Step Two: x-5=6

Step Three: x=11

Number Three:
(image)

Number One) Solutions please: f(x)= (x−1)^2−36 ____________________________________________________________________ Number-example-1
User Bartando
by
4.6k points

1 Answer

4 votes

Answer:

Explanation:

(1)
f(x) = (x-1)^(2) - 36

First, let's expand the expression:


f(x) = x^(2) -2x + 1 - 36


f(x) = x^(2) - 2x - 35

Next, let's factor the quadratic:


f(x) = (x - 7)(x + 5)

Finally, set the equation equal to
0 to find the solutions


0 = (x - 7)(x + 5)


x = -5, 7

(2) During the step
(x - 5)^(2) = 36, when you take the square root of both sides, you have two equations, rather than one:


x - 5 = 6 and
x - 5 = -6, so the solutions should be
x = -1, 11

(3)


(1)/(4)(x + 5)^(2) - 1 = 3

Add
1 to both sides


(1)/(4)(x + 5)^(2) = 4

Multiply both sides by
4


(x + 5)^(2) = 16

Take the square root of both sides


x + 5 =±
4

Subtract
5 from both sides


x = -9, -1

User Jonathan Gurebo
by
4.4k points